Payment of "Pisuke" Money in Sasak Traditional Marriages (Case Study in Sakra District, East Lombok) - Anwar; Fahrul Razi; Lalu Muhammad Nurul Wathoni (al-Afkar, Journal For Islamic Studies, 2025)
This study briefly describes the process of paying the Pisuke money according to Sasak traditional wedding traditions. The Sasak people are known for their diverse and unique traditions. The tradition of elopement, or elopement, is a long-standing tradition that still exists today among the Sasak people. Within this tradition, a process called Pisuke is part of the local wisdom of the Sasak people and is a cultural treasure. The payment of Pisuke has been carried out by most people using money, the aim being to simplify the payment process and its use. This tradition has been passed down through generations by the Sasak people. Therefore, in several villages in Sakra District, the community has agreed and requires the payment of Pisuke money, both for marriages with people domiciled in the same village and especially with people from other villages. Because the payment of Pisuke money in Sakra District precedes the marriage contract, the marriage contract will be delayed if the payment of Pisuke is delayed. The pisuke money itself is given by the groom to the bride, for a family thanksgiving ceremony, inviting close neighbors. The pisuke money is also used to purchase household supplies for the bride and groom, with the remainder going to other expenses.